Nonthermal activation of transient receptor potential vanilloid-1 channels in abdominal viscera tonically inhibits autonomic cold-defense effectors - Steiner, Alexandre A.; Turek, Victoria F.; Almeida, Maria C. [UNESP]; Burmeister, Jeffrey J.; Oliveira, Daniela L.; Roberts, Jennifer L.; Bannon, Anthony W.; Norman, Mark H.; Louis, Jean-Claude; Treanor, James J.S.; Gavva, Narender R.; Romanovsky, Andrej A. (Society for Neuroscience, 2007)
An involvement of the transient receptor potential vanilloid (TRPV) 1 channel in the regulation of body temperature (T b) has not been established decisively. To provide decisive evidence for such an involvement and determine its mechanisms were the aims of the present study. We synthesized a new TRPV1 antagonist, AMG0347 [(E)-N-(7-hydroxy-5,6,7,8-tetrahydronaphthalen-1- yl)-3-(2-(piperidin-1-yl)-6-(trifluoromethyl)pyridin-3-yl)acrylamide], and characterized it in vitro. We then found that this drug is the most potent TRPV1 antagonist known to increase T b of rats and mice and showed (by using knock-out mice) that the entire hyperthermic effect of AMG0347 is TRPV1 dependent. AMG0347-induced hyperthermia was brought about by one or both of the two major autonomic cold-defense effector mechanisms (tail-skin vasoconstriction and/or thermogenesis), but it did not involve warmth-seeking behavior. The magnitude of the hyperthermic response depended on neither T b nor tail-skin temperature at the time of AMG0347 administration, thus indicating that AMG0347-induced hyperthermia results from blockade of tonic TRPV1 activation by nonthermal factors. AMG0347 was no more effective in causing hyperthermia when administered into the brain (intracerebroventricularly) or spinal cord (intrathecally) than when given systemically (intravenously), which indicates a peripheral site of action. We then established that localized intra-abdominal desensitization of TRPV1 channels with intraperitoneal resiniferatoxin blocks the T b response to systemic AMG0347; the extent of desensitization was determined by using a comprehensive battery of functional tests. We conclude that tonic activation of TRPV1 channels in the abdominal viscera by yet unidentified nonthermal factors inhibits skin vasoconstriction and thermogenesis, thus having a suppressive effect on T b. Copyright © 2007 Society for Neuroscience.
Keywords: Afferent; Channel; Chemosensory; Hyperthermia; Temperature; TRPV1; 3 (4 tert butylphenyl) n (2,3 dihydrobenzo[1,4]dioxin 6 yl)acrylamide; amg 0347; amg 9810; n (7 hydroxy 5,6,7,8 tetrahydronaphthalen 1 yl) 3 [2 (piperidin 1 yl) 6 (trifluoromethyl)pyridin 3 yl]acrylamide; protein inhibitor; resiniferatoxin; transient receptor potential vanilloid 1 antagonist; unclassified drug; vanilloid receptor 1; abdominal wall musculature; animal cell; animal experiment; animal model; behavior; controlled study; defense mechanism; desensitization; drug synthesis; female; gene activation; hyperthermia; in vitro study; knockout mouse; mouse; nonhuman; priority journal; rat; rodent; skin temperature; thermogenesis; vasoconstriction; Abdominal Cavity; Acrylamides; Animals; Autonomic Nervous System; Body Temperature; Body Temperature Regulation; CHO Cells; Cold; Cricetinae; Cricetulus; Diterpenes; Fever; Humans; Mice; Mice, Knockout; Pyridines; Rats; Skin; Skin Temperature; Thermogenesis; TRPV Cation Channels; Vasoconstriction; Viscera